1980
DOI: 10.1530/jrf.0.0600247
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotective effects of some amides on rabbit spermatozoa

Abstract: Semen was diluted 1:9 with egg yolk-citrate medium containing 0.31--3.1 M (final concentration) formamide, butyramide, acetamide, propionamide, dimethylformamide, lactamide, malomide, ethylene glycol, trimethylene glycol, dimethylsulphoxide (DMSO) or glycerol. After 30 min incubation at 20 degrees C, sperm motility was superior in hypertonic solutions of acetamide, lactamide, dimethylsulphoxide, trimethylene glycol and ethylene glycol. Some of these compounds were added to semen diluted 1:2 in an isotonic egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 9 publications
1
31
0
1
Order By: Relevance
“…Discrepancies may be partly because of the fact that the composition of acetamide extender used by these authors (acetamide egg yolk HEPES extender with glucose, lactose and raffinose) was very different from that used in the present study (egg yolk Tris-based extender). Other smallscale experiments using 1 and 2 M Me 2 SO (Hanada andNagase, 1980 andKashiwazaki et al, 2006, respectively) showed no differences between Me 2 SO and acetamide as cryoprotectants for rabbit sperm freezing. On the contrary, several authors have demonstrated the efficient sperm protection of 3.0 and 3.5 M Me 2 SO in rabbit sperm cryopreservation Viudes de Castro and Vicente, 1996;Mocé et al, 2003;Cortell and Viudes de Castro, 2008;Iaffaldano et al, 2012;Rosato and Iaffaldano, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Discrepancies may be partly because of the fact that the composition of acetamide extender used by these authors (acetamide egg yolk HEPES extender with glucose, lactose and raffinose) was very different from that used in the present study (egg yolk Tris-based extender). Other smallscale experiments using 1 and 2 M Me 2 SO (Hanada andNagase, 1980 andKashiwazaki et al, 2006, respectively) showed no differences between Me 2 SO and acetamide as cryoprotectants for rabbit sperm freezing. On the contrary, several authors have demonstrated the efficient sperm protection of 3.0 and 3.5 M Me 2 SO in rabbit sperm cryopreservation Viudes de Castro and Vicente, 1996;Mocé et al, 2003;Cortell and Viudes de Castro, 2008;Iaffaldano et al, 2012;Rosato and Iaffaldano, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, differences in reproductive parameters have been observed with fresh (Bolet et al, 2000;Vicente et al, 2000) and cryopreserved sperm belonging to different breeds or lines of rabbits. Rabbit spermatozoa are relatively sensitive to cryoprotectants containing hydroxyl groups such as glycerol, compared with those containing amide or methyl groups (Hanada and Nagase, 1980;Chen et al, 1989;Castellini et al, 1992). In this context, the basic ingredients of current sperm-freezing extenders in rabbits are a combination of permeating cryoprotectants such as acetamide or dimethyl sulphoxide (Me 2 SO) and non-permeating cryoprotective agents such as lactose, sucrose, raffinose or trehalose.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that 1.0 M lactamide had a higher cryoprotective effect than 1.0 M glycerol in the cryopreservation of Japanese white rabbit spermatozoa. To date, the effects of some cryoprotectants on post-thaw sperm characteristics have been compared by Hanada and Nagase [12] and Dalimata and Graham [15]. In the study by Hanada and Nagase, 1.0 M lactamide, acetamide, and DMSO were highly cryoprotective for the New Zealand white rabbit, and 1.0 M glycerol resulted in extremely low motility after thawing.…”
Section: Discussionmentioning
confidence: 99%
“…In early research on freezing of rabbit spermatozoa, spermatozoa frozen with glycerol resulted in extremely low fertility [8][9][10][11]. After 1980, studies employing acetamide [12][13][14][15] or DMSO [12,[16][17][18][19][20][21][22] as a cryoprotectant have been encouraging. H o w e v e r , t h e r e i s a l i t t l e i n f o r m a t i o n o n cryoprotectants when freezing Japanese white rabbit spermatozoa.…”
mentioning
confidence: 99%
“…Studies describing freezing techniques for JW rabbit sperm found that 1.0 M lactamide and acetamide were more suitable than 1.0 M glycerol and dimethyl sulphoxide (DMSO) as cryoprotectants (Kashiwazaki et al, 2006). DMSO, acetamide, and lactamide were found to be effective cryoprotectants for New Zealand white rabbit sperm (Hanada and Nagase, 1980); however, DMSO, ethylene glycol, and glycerol were not successful when freezing semen from Dutch Belted rabbits. The differing efficacies of the various cryoprotectants indicate that there are species-specific differences which must be accounted for when designing appropriate freezing protocols (Dalimata and Graham, 1997).…”
Section: Fertilisation Capacity Of Post-thaw Spermatozoa Cooled At -0mentioning
confidence: 99%